Fly Ash Nanoparticles Assisted Foam Injection Water Alternating Gas for Enhanced Oil Recovery - MING, PHONG GUAN (2021)

(untitled)
The success of foam injection as a displacing fluid in the porous media mainly depends on the stability of the foam.